Α‐synuclein RT‐QuIC in cerebrospinal fluid of LRRK2‐linked Parkinson's disease. Issue 6 (9th May 2019) - Garrido, Alicia; Fairfoul, Graham; Tolosa, Eduardo S.; Martí, Maria José; Green, Alison; ,
Abstract: Background: Leucine‐rich kinase 2 (LRRK2)‐linked Parkinson's disease (PD) is clinically indistinguishable from idiopathic PD (IPD). A pleiotropic neuropathology has been recognized but the majority of studies in LRRK2 p.G2019S patients reveal Lewy‐type synucleinopathy as its principal histological substrate. To date no in vivo biomarkers of synucleinopathy have been found in LRRK2 mutation carriers. Objectives: We used real‐time quaking‐induced conversion (RT‐QuIC) technique to assess the presence of alpha‐synuclein (a‐syn) aggregates in cerebrospinal fluid (CSF) of LRRK2 p.G2019S carriers. Methods: CSF samples of 51 subjects were analyzed: 15 LRRK2 p.G2019S PD, 10 IPD, 16 LRRK2 p.G2019S nonmanifesting carriers (NMC) and 10 healthy controls. The presence of parkinsonism and prodromal symptoms was assessed in all study subjects. Results: Forty percent ( n  = 6) LRRK2‐PD, and 18.8% ( n  = 3) LRRK2‐NMC had a positive a‐syn RT‐QuIC response. RT‐QuIC detected IPD with 90% sensitivity and 80% specificity. No clinical differences were detected between LRRK2‐PD patients with positive and negative RT‐QuIC. A positive RT‐QuIC result in LRRK2‐NMC occurred in a higher proportion of subjects meeting the Movement Disorder Society research criteria for prodromal PD. Interpretation: RT‐QuIC detects a‐syn aggregation in CSF in a significant number of patients with LRRK2‐PD, but less frequently than in IPD. A small percentage of LRRK2‐NMC tested also positive. If appropriately validated in long‐term studies with large number of mutation carriers, and hopefully, postmortem or in vivo confirmation of histopathology, RT‐QuIC could contribute to the selection of candidates to receive disease modifying drugs, in particular treatments targeting a‐syn deposition.